Reflexo do nível de agressividade fiscal sobre a rentabilidade de empresas listadas na BM&FBOVESPA e NYSE - Araújo, Risolene Alves de Macena (2017)
The present research aims to analyze the effects of the level of tax aggressiveness on the profitability of the companies listed on BM&FBOVESPA and NYSE. Regarding the final sample of the research, it was composed by three perspectives: (i) when BTD was considered as parameter for determination of the independent variable, the final sample was 1429 companies (244 of BM & FBOVESPA and 1363 of NYSE); (Ii) when considering ETR, 1418 companies (246 of BM & FBOVESPA and 1174 of NYSE); And (iii) when considering CashETR, 1321 companies (143 of BM&FBOVESPA and 1178 of NYSE). To reach the objective of this research, a search hypothesis was generated for each stock exchange. Then, a mean comparative test of fixed effects was applied. In addition, an estimation was made by means of quantum regression (RQ). The results of the model composed by the non-financial companies listed on the BM&FBOVESPA indicate that, on average, the NAGGETR and NAGGCashETR negatively influence the ROA of the companies, being adverse to the expected ones. With the NAGGBTD, the ratio was positive (expected), indicating that companies that present higher accounting book profit than taxable profit lead to higher profitability. Regarding RQ, the results followed the evidences of the average tests, with the exception of NAGGCashETR, which in addition to the coefficient signal change, it became no longer significant; And the NAGGBTD, in the 50th qunatile, which did not present significance. The results for the model that contains the companies listed on NYSE also indicate that, on average, the NAGGETR and NAGGCashETR negatively influence the profitability of the companies. On the other hand, the relationship between the NAGGBTD and the ROA was positive (adverse to the expected), that is, the companies that presented the accounting book profit higher than the taxable one led to the higher returns. Regarding RQ, the results followed the evidence from the mean tests, except for the NAGGETR 75, which ceased to be significant. It should also be pointed out that, as in BM&FBOVESPA, the most intense relations between the level of tax aggressiveness and profitability occurred in the quantil 25. It is understood, therefore, that the companies with the lowest returns are the ones that are most influenced By the highest levels of aggressiveness. Furthermore, the fact that the results obtained from the BM&FBOVESPA context are not compatible with previous studies, in relation to NAGGETR and NAGGCashETR it is acceptable, since the methodology that was used segregated the levels of tax aggressiveness according to the mean of the ETR practiced In the sector, and not the general average, as applied in other studies. As well, due to the fact that a mo reconservative behavior of the market that has a large concentration of family businesses, such as Brazil, that is expected. The contribution of this research to the literature is the demonstration of the reflexes that the levels of tax aggressiveness exert on the profitability of companies in the capital market, taking into considaration the economic sector to which it is inserted. As well, for conducting a comparative analysis between capital markets and tax legislation at different levels of development (Brazil vs. USA). In addition, it fills some gaps in this area by adding results to the existing literature.